Water-in-oil droplet-mediated method for detecting and isolating infectious bacteriophage particles via fluorescent staining - Hoshino, Miu; Ota, Yuri; Suyama, Tetsushi; Morishita, Yuji; Tsuneda, Satoshi; Noda, Naohiro (Frontiers in Microbiology, 2023)
Bacteriophages are the most abundant entities on Earth. In contrast with the number of phages considered to be in existence, current phage isolation and screening methods lack throughput. Droplet microfluidic technology has been established as a platform for high-throughput screening of biological and biochemical components. In this study, we developed a proof-of-concept method for isolating phages using water-in-oil droplets (droplets) as individual chambers for phage propagation and co-cultivating T2 phage and their host cell Escherichia coli within droplets. Liquid cultivation of microbes will facilitate the use of microbes that cannot grow on or degrade agar as host cells, ultimately resulting in the acquisition of phages that infect less known bacterial cells. The compartmentalizing characteristic of droplets and the use of a fluorescent dye to stain phages simultaneously enabled the enumeration and isolation of viable phage particles. We successfully recultivated the phages after simultaneously segregating single phage particles into droplets and inoculating them with their host cells within droplets. By recovering individual droplets into 96-well plates, we were able to isolate phage clones derived from single phage particles. The success rate for phage recovery was 35.7%. This study lays the building foundations for techniques yet to be developed that will involve the isolation and rupturing of droplets and provides a robust method for phage enumeration and isolation.